Architecture and Empathy. Charles W. Moore (1925-1993) - Martínez Martínez, Raúl (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
This article shows how the aesthetic and philosophical concept of Empathy (Einfühlung), aided by the psychology, was incorporated into the field of architectural theory; first, in the German-speaking context with Theodor Lipps at the end of the nineteenth century, and then, in the Anglo-American context with key personalities such as Bernard Berenson and, his pupil, Geoffrey Scott. It will expose the enormous influence that Scott exerted in the early fifties and sixties in the United States with his masterwork, The Architecture of Humanism. A Study in the History of Taste (1914). To illustrate this, the article will examine the case study of the American architect Charles W. Moore (1925-1993). It will focus on one of his most influential works, the Sea Ranch (1963-65) condominium, to exemplify the empathetic and corporeal attitude that he defended as a professor and architect. It will do so through four categories that became design elements for many of his houses in the sixties: Place, Body Image, Intermediate Spaces, and the Architectural Experience.